Yoga and moral values - Shankar, Ganesh 1958- (New Delhi, India Satyam Publ. House, 2008)
Papers presented at the National Seminar on Yoga and Moral Values, held at Sagar during 29-31 January 2006
Includes bibliographical references. - English and Hindi
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Yoga -- Congresses; Yoga -- Congresses -- Therapeutic use; Values -- Congresses; Aufsatzsammlung; Konferenzschrift